Filogenia e diversidade de Xyridaceae Neotropicais, com ênfase no gênero Xyris - Nara Furtado de Oliveira Mota (2014)
The family Xyridaceae includes five genera of petaloid monocots, distributed mainly in tropical and subtropical regions. Four of the five genera, Abolboda (23 species), Aratitiyopea (one species), Achlyphylla (one species), and Orectanthe (two species) are restricted to South America and the latter three are exclusive to the Guiana Shield, in Northern South America. Xyris, the largest genus of the family, with about 400 species, is the most widespread of them, occurring in tropical and subtropical regions of the Americas, Africa, Asia and Australia and, in some temperate areas. Xyridaceae have been poorly sampled in phylogenetic studies, either using morphological and/or molecular data. Therefore the position of the family is controversial within the clade of Commelinids and the infrageneric classification of the largest genus remained obscure. This thesis is divided into two chapters: 1. Phylogeny o Xyris with emphasis on South American species; and 2. Xyridaceae of the Viruá National Park, Roraima state, Brazil, with emphasis on the genus Xyris. Both studies were based on samples collected during fieldwork between 2008 and 2013 and in the herbarium samples. To better understand the richness, biogeography and evolution of the group, over 30 field trips were conducted throughout the Brazilian territory, in order to sample the largest number of habitats and covering the morphological and taxonomical diversity of the genus. A total of 718 samples were collected, comprising approximately 137 species of Xyridaceae. Samples from Australia, North and Central America, provided by the New York Botanical Garden, were also included in the analyses. For the phylogeny of the genus Xyris five markers were investigated: two mitochondrial (cox3 and orf25) and three plastid (matK, ndhF and rbcL) and parsimony, maximum likelihood and Bayesian analyses were performed. As a result within Xyris, the Australian species of Xyris form a clade sister to the American species (Chapter 1). All sections of Xyris were recovered – Xyris sect. Pomatoxyris and Xyris sect. Nematopus and Xyirs sect. Xyris. However, Xyris sect. Pomatoxyris had a small sampling (< 10 %) and, to confirm its monophyly, a wider sampling is required. Within Xyris sect. Nematopus, seven clades were highlighted and discussed based on at least one of the following three parameters: high to moderate support; species are morphologically similar; and species present similar biogeographic patterns. This study consists of the first phylogenetic approach to the family with an satisfactory sampling; generating new questions to be investigated regarding of the infrageneric classification. In the second chapter, as a result of field work for the phylogeny sampling and a deep herbarium investigation, a flora of the Viruá National Park, in Roraima, Brazil, was elaborated for the species of Xyridaceae. The flora includes detailed morphological descriptions, dichotomous keys, plates and images of scanning electron microscopy of the seeds. Sixteen species of Xyris, and four Abolboda were recorded in the Park and a new synonym is proposed. These studies represent an advance in understanding the infrageneric classification of Xyris in a phylogenetic context, and guiding future actions to find most informative markers and guiding the future field works to areas poorly sampling yet, such as Africa, Asia and Australia.